“Analyzing future perspectives of renewable energy in Democratic Republic of Congo using Integrated Assessment Model (IAM/GCAM-EML)” - MBONGO CHARLY KINDEMO (Graduate School of International Studies Ajou University, 2024)
The energy landscape in the Democratic Republic of Congo presents a juxtaposition. Despite abundant energy potential, particularly in renewable resources, the country contends with one of the lowest electricity access rates in Africa. This paradox has prompted the Democratic Republic of Congo Government to prioritize "universal energy access" since 2014 and focus on leveraging renewable energy sources. In the energy sector, hydroelectric power, primarily through the Inga dam, plays a pivotal role in meeting the country's energy needs. However, due to the geographical limitations and costs associated with the Inga Dam, it cannot fully cover the entire nation's requirements. Given the substantial solar energy potential in the Democratic Republic of Congo, tapping into solar energy offers a promising pathway for decentralizing the electricity sector and bolstering the electrification rate across the country. This thesis is dedicated to amplifying the proportion of electricity generated from solar sources in the Democratic Republic of Congo. To achieve this goal, an energy modeling tool (Global Change Assessment Model- Energy Modeling Lab: GCAM-EML) was utilized to explore various scenarios. These scenarios examined how the share of solar power generation in the electricity mix might evolve based on the assumptions laid out in this study. The decreased costs in the PV scenario facilitated a greater supply of solar power generation. This resulted in an increase in its contribution from 0.23% in 2020 to 16.88% in 2030 and further to 30.01% by 2040. This study also revealed a future decrease in energy consumption within the building sector, resulting in a more prominent position for the industrial sector between 2030 and 2040. Despite industries currently being the major electricity consumers, it is projected that by 2040, the building sector will marginally surpass industrial usage by 2%, according to simulation results. Among the four scenarios assessed in this study, it was evident that only three—namely, the Reduced biomass, PV, and Combined scenarios—substantially reduced the Carbon Dioxide (CO2) emissions. However, the Lowhydro scenario led to a significant increase in the Carbon Dioxide (CO2) emissions. Given these findings, this research demonstrates the potential for the country to achieve its goals outlined in the Nationally Determined Contributions (NDCs) by elevating the share of solar energy and concurrently reducing the Carbon Dioxide (CO2) emissions. Key words: Global Change Assessment Model-Energy Modeling Lab, Renewable, Inga dam, hydroelectric power, Solar energy, Democratic Republic of Congo, Share
학위논문(석사)--융합에너지학과,2024. 2
Keywords: Increasing the share of solar energy